Divulgación científica en YouTube: comparativa entre canales institucionales vs. influencers de ciencia - Dr. Álex BUITRAGO,Mgt. Lidia TORRES-ORTIZ (Fonseca, Journal of Communication, 2023)
In recent years, independent communicators from virtually all academic, cultural and scientific fields have emerged on YouTube; also known as science influencers. At the same time, traditional academic and scientific institutions have joined the phenomenon of digital outreach by launching their own YouTube channels, as is the case of the Scientific Culture and Innovation Units (UCC+i) of most Spanish universities.